Peran Komitmen Profesional Antara Work Life Balance dan Kepuasan Kerja Guru Tingkat Menengah Atas - Febry Dwi Rismayanti; Yohanes Arianto Budi Nugroho (Journal of Applied Management Research, 2022)
This research aims to prove whether the influence of Work life balance on Job Satisfaction mediated by Professional Commitment. The research was conducted by disseminating research tools in the form of questionnaires to some people of DKI Jakarta who have professions as teachers at the high school level by using random clustering sampling techniques. The sample in this study numbered 55 respondents. Data processing is done using the help of applications in the form of IBM SPSS software version 26.0 for Windows with Process v3.5 by Andrew F. Hayes. The results of the study have shown (1) a significant positive influence between Work life balance and Professional Commitment. (2) The same happens to the influence of Professional Commitment with Job Satisfaction. (3) There are also significant positive results between Work life balance and Job Satisfaction. (4) However, the results showed that there is no mediation role of Professional Commitment in this research model.Keywords : Work Life Balance, Professional Commitment, Job Satisfaction